Analisis Penerapan Teknologi Digital & Persepsi Risiko Teknologi dalam Audit Dapat Mempengaruhi Pandangan Mahasiswa Terhadap Kualitas Audit Digital - Alfina Rianti; Adis Brilianti; Anisa Rahmawati; Angelina Febrina; Dian Sastra; Heberyani Br. Tarigan; Ika Ayu Lestari; Irvina Rahimatullah Sofian; Jovita Eklesia Pardede; Meiyo Glori Tarigan; Melly N. Kusuma; Saskia Mariana Putri; Yesra Wani Purba; Yuafni Sepditami; Yuyun Tamila (Universitas Warmadewa, 2025)
This study aims to analyze the impact of digital technology implementation and technology risk perception on accounting students' views regarding the quality of digital audits. Using a quantitative approach, data were collected through surveys involving 80 accounting students from the University of Palangka Raya. The analysis revealed that digital technology implementation significantly enhances the quality of digital audits (B = 0.496; p < 0.05), while technology risk perception also positively influences audit quality, albeit to a lesser extent (B = 0.406; p < 0.05). The regression model yielded an R² value of 0.664, indicating that the two independent variables explain 66.4% of the variation in digital audit quality. This study underscores the importance of integrating digital technology into audits and managing risk perceptions through proper training to support audit effectiveness in the digital era.